2015
DOI: 10.1155/2015/787069
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia among Adult Patients who Underwent Surgery for Esophageal Atresia at Birth

Abstract: BACKGROUND: Clinical experiences of adults who underwent surgery for esophageal atresia at birth is limited. There is some evidence that suggests considerable long-term morbidity, partly because of dysphagia, which has been reported in up to 85% of adult patients who undergo surgery for esophageal atresia. The authors hypothesized that dysphagia in this population is caused by dysmotility and/or anatomical anomalies.OBJECTIVE: To determine the motor and anatomical causes of dysphagia.METHODS: A total of 41 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…It is found in children (2, 3, 7, 14, 15, 17, 2730) and persist throughout life as demonstrated by adult studies (4, 1113, 15, 16). Esophageal dysmotility in EA was recently described using high-resolution manometry (HREM) with three types of abnormalities observed: aperistalsis (Figure 1), isolated distal contractions (Figure 2), and pressurization (2, 3, 19).…”
Section: Characterization Of Esophageal Dysmotilitymentioning
confidence: 89%
See 1 more Smart Citation
“…It is found in children (2, 3, 7, 14, 15, 17, 2730) and persist throughout life as demonstrated by adult studies (4, 1113, 15, 16). Esophageal dysmotility in EA was recently described using high-resolution manometry (HREM) with three types of abnormalities observed: aperistalsis (Figure 1), isolated distal contractions (Figure 2), and pressurization (2, 3, 19).…”
Section: Characterization Of Esophageal Dysmotilitymentioning
confidence: 89%
“…Esophageal motility has been assessed in children and adults with EA by esophageal manometry [water perfused (4, 1116) or high resolution (2, 3, 7, 1719)], impedancemetry (19, 20), or videofluoroscopy (21, 22). Studies have reported anomalies at each level of the esophagus including larynx and vocal cords (23–25) and gastric motor function (15, 26).…”
Section: Characterization Of Esophageal Dysmotilitymentioning
confidence: 99%
“…Huynh Trudeau et al (2015) found dysphagia in 73% of EA/ TEF adult patients. 21 Dysphagia is most likely caused by a certain dysmotility or by anatomic anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Huynh Trudeau et al (2015) found dysphagia in 73% of EA/ TEF adult patients. 21 Dysphagia is most likely caused by a certain dysmotility or by anatomic anomalies. 21 Overall, dysphagia is a well-known long-term complication contributing to EA/TEF morbidity and may impair routine family life to the outer extend in that EA/TEF patients deny regular eating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation